(untitled) (Mongolian Journal of Agricultural Sciences, 2021)
Cryptosporidium is a small protozoan parasite that infects the microvillous region of epithelial cells in the digestive and respiratory tract of vertebrates. It is an obligate intracellular parasite of man and other mammals, birds, reptiles and fish. We were purification Cryptosporidium spp. oocysts with saturated sugar solution from diarrhea cattle. And experimental infection use by control C. parvum (Germany) strain and Cryptosporidium spp. with oral 1x107 oocyst/ml doses in per BALB/c mouse. Post inoculation detected Cryptosporidium oocysts within a week in the feces mice and counted average Cryptosporidium spp. (Mongolia) 1.033±0.2x106 (p<0.025) and C. parvum 0.9±0.05x106 (p<0.001) oocyst/ml each other period of the experiment. Mice from the control and experimental trials were slaughtered on the 30th day post inoculation and examination for pathology. Pathology examination, the asexual and sexual developmental stages of Cryptosporidium were evident in the gastric and small intestinal epithelium of the experimental mice, in oocysts, in the glandular layer of gastric submucosa, and in the microvillous of small intestinal wall submucosa. In the future, we will do focus of molecular biological and isolated Mongolian laboratory strain of Cryptosporidium spp.. Cryptosporidium spp. үүсгэгчийг BALB/c хулганад зориудын халдвар хийж туршсан дүн Криптоспорид бүх төрлийн сээр нуруутан амьтдын ходоод, нарийн гэдэсний хучуур эсэд шимэгчилдэг эгэл биетэн. Бид усархаг чацга алдсан үхрийн баасны сорьцоос криптоспоридын ооцистыг сахарын ханасан уусмалаар цэвэршүүлэн авлаа. Монгол дахь уг үүсгэгчийг 1х107 ооцист/мл тунгаар BALB/c үүлдрийн хулганад зориудын халдвар хийж, хяналтаар С. parvum (Герман) омгийг ашиглав. Халдвар хийснээс хойш 7 хоногийн дараагаас эхлэн туршилтын бүлэг тус бүрийн хулганы баасаар криптоспоридын ооцист ялгарч, туршилтын нийт хугацаанд дунджаар монгол дахь криптоспоридын үүсгэгч 1.033±0.2х106 (p<0.025), C. parvum зүйлийн 0.9±0.05x106 (p<0.001) ооцист/мл тоологдлоо. Хяналт, туршилтын бүлгийн хулганыг халдвар хийснээс хойш 30 дахь хоногт нядалж эмгэг бүтцийн өөрчлөлтийг судлав. Туршилтын бүлгийн хулганы ходоод, нарийн гэдэсний ханын хучуур эсүүд гэмтэж, үүсгэгчийн ооцист ихээхэн халдварлаж, ходоодны ханын салст бүрхүүлийн булчирхайлаг эдийн давхаргад байршин шимэгчилжээ. Нарийн гэдэсний бичил цэлмэнгийн ёроол хэсгээр криптоспоридын бэлгийн бус, бэлгийн хөгжлийн үе шатууд тод илрэв. Бид хоруу чанар өндөр Cryptosporidium spp.-ийн лабораторийн омог гарган авахаар ажиллаж байна. Түлхүүр үг: C. parvum омог, баасны сорьц, ооцист, үхэр, Гематоксилин-Эозин будаг, сахарын ханасан уусмал